Pre-supernova neutrinos at Super-Kamiokande with gadolinium - Simpson, CH (2019)
Supernova detection is a major objective of the Super-Kamiokande (SK) ex- periment. In the next stage of SK (SK-Gd), gadolinium (Gd) sulfate will be added to the detector, which will improve the ability of the detector to iden- tify neutrons. A core-collapse supernova will be preceded by an increasing flux of neutrinos and anti-neutrinos, from thermal and weak nuclear pro- cesses in the star, over a timescale of hours; some of which may be detected at SK-Gd. This could provide an early warning of an imminent core-collapse supernova, hours earlier than the detection of the neutrinos from core col- lapse. Electron anti-neutrino detection will rely on inverse beta decay events below the usual analysis energy threshold of SK, so Gd loading is vital to reduce backgrounds while maximising detection effciency. Assuming normal neutrino mass ordering, more than 200 events could be detected in the final 12 hours before core collapse for a 15-25 solar mass star at around 200 pc, which is representative of the nearest red supergiant to Earth, alpha Ori (Betel- geuse). At a statistical false alarm rate of 1 per century, detection could be up to 10 hours before core collapse, and a pre-supernova star could be de- tected by SK-Gd up to 600 pc away. A pre-supernova alert could be provided to the astrophysics community following gadolinium loading.